Development and Validation of Biology Attitude Scale for Secondary School Students in Islamabad, Pakistan - Shahzad Ahmad,Sadia Jamil (JCTE, 2023)
The aim of present study was to develop and validate an instrument to measure attitude of Students towards learning biology at 9th grade. It is imperative to ensure students’ positive attitude towards biology at 9th grade as research has suggested that both attitude and achievement are inter-dependent. In order to develop the scale, a draft of 40 items on seven different constructs was developed after discussion with experts. The draft scale, was pilot tested on 200 grade 9 biology students (girls=97, boys=103). To determine construct validity, exploratory factor analysis with varimax rotated method was performed. Final scale reduced to 26 items with seven factors explaining 52.2% of the total variance. Overall, Cronbach’s alpha reliability coefficient of the biology attitude scale was found 0.81. In view of above results, it is concluded that the developed scale is reliable and valid measurement tool for assessing students’ attitude towards biology at secondary level.